Apport d'un programme de génétique à une filière de production aquacole : l'exemple de l'ostréiculture - Lapegue, Sylvie; Bedier, Edouard; Goyard, Emmanuel; Degremont, Lionel; Baud, Jean-pierre; Gerard, Andre; Goulletquer, Philippe; Boudry, Pierre (Styli 2003. Trente ans de crevetticulture en Nouvelle-Calédonie. Nouméa - Koné, 2-6 juin 2003. 2004. Gorarant C, Harache Y, Herbland A, Mugnier C. Ed. Ifremer, Actes de Colloque, n°38, pp.113-120, 2004)
Two oyster species are currently present along the French coasts : the indigenous European flat oyster (Ostrea edulis), and the Pacific cupped oyster (Crassostrea gigas), that has been introduced from Japan since the beginning of the 70ies. The flat oyster successively suffered from two protozoan diseases during the 60ies and its production decreased from 20 000 tons/year by that time to 1 500 tons/year nowadays. Consequently, the oyster production is principally (99%) based upon the Pacific oyster species with approximately 150 000 tons/year among which 90% are grown from the natural spat. However, the hatchery production of this species is developing and was estimated to 400 to 800 millions spat in 2002. Moreover, strengthened relationships between IFREMER and the 5 commercial hatcheries, that all joined the SYSAAF (Union of the French poultry, shellfish and fish farming selectors), allow to plan for new genetic breeding programs. At the end of the 80ies, IFREMER initiated a genetic breeding program for the resistance of the European flat oyster to the bonamiosis, and obtained strains more tolerant to this disease. After two generations of massal selection, molecular markers had identified a reduced genetic basis in this program. It was then reoriented to an intra-familial selection. However, we were confronted to a zootechnic problem to manage such a scheme and we compromised by an intra-cohorts of families selection scheme managed using molecular markers. The program has now reached the transfer level with experimentation at a professional scale. Concerning the Pacific cupped oyster, and in parallel with the obtaining and the study of polyploids, performance of different Asian cupped oyster strains were compared to the one introduced in France thirty years ago and currently suffering from summer mortalities. The local strain exhibited better performance, certainly based upon a good local adaptation. In other respects, although early growth is a relevant criteria for selection for growth to commercial stage, ...